The effects of sodium butyrate on Hox gene expression in a human colorectal adenocarcinoma cell line, HT29. - Conaty, Lucy D. (East Carolina University, 2013)
Hox genes are a subgroup of the large family of homeobox containing genes, known to pattern anterior/posterior and proximal/distal axes during embryonic development. More recently Hox gene research has focused on the role of these genes during carcinogenesis. We studied the pattern of Hox gene expression in a human colorectal adenocarcinoma cell line, HT29, in response to treatment with a histone deacetylase inhibitor, sodium butyrate. Sodium butyrate treatment has been previously described to differentiate HT29 cells. The cells acquire differentiated characteristics after a seven-day treatment period with 5 mM sodium butyrate. These features include increased microvilli concentrations, tight junctions, and the formation of apical and basolateral domains. Our research aimed to study the role of Hox genes in colorectal cancer by analyzing their expression in both proliferative and growth-inhibited HT29 cells. The first phase of our research was to determine the pattern of expression for all 39 characterized human Hox genes using RT-PCR in order to select genes of interest that are differentially between proliferating and differentiated HT29 cells. The second was to verify the differential expression of these genes with qRT-PCR and Western blot. It was observed that most genes of cluster D were expressed in untreated but not treated HT29 cells. More specifically, D8 and D9 were the only two genes of this cluster with a differential pattern of expression than the other genes of their paralog groups. We hypothesized that D8 and D9 are responsible for maintaining the proliferative, undifferentiated state of the HT29 cells. Using qRT-PCR analysis, D8 was shown to be up-regulated in untreated HT29 cells in comparison to treated HT29 when normalized to housekeeping genes. However, D9 was shown to be down-regulated in untreated HT29 in comparison to treated HT29 when normalized to housekeeping genes. The Western blot for Hox D9 reflected the findings of RT-PCR but not qRT-PCR. Protein expression was present in untreated HT29 cell lysates, but not the sodium butyrate treated lysates. D8 showed no protein expression in either untreated or treated cell lysates. The effects of sodium butyrate treatment on HT29 cell proliferation and differentiation was assessed using growth curves and ultrastructural analysis by transmission electron microscopy. It was observed that when cells are seeded at a low density (9.6 x 10⁴) and recorded for seven days, sodium butyrate treatment effectively inhibited cellular proliferation. Electron micrographs showed that NaBT treated HT29 cells exhibited potential apical domains, increased concentrations of microvilli, tight junctions and approximately double the number of desmosomes at intercellular junctions. In addition, some of the treated cells exhibited the formation of mucin granules, specific to the phenotype of epithelial goblet cells.
Keywords: Biology, Molecular; Molecular biology; Gene expression; Homeobox genes; Histones; Adenocarcinoma; Colon (Anatomy)--Cancer; Rectum--Cancer